Spontaneous pneumothorax in paracoccidioidomycosis patients from an endemic area in Midwestern Brazil - Cabrera, Lucas G. G.; Santos, Aline F.; Andrade, Ursulla V.; Guedes, Carlos Ivan A.; Oliveira, Sandra M. V. L.; Chang, Marilene R.; Mendes, Rinaldo P. [UNESP]; Paniago, Anamaria M. M. (Wiley-Blackwell, 2017)
Paracoccidioidomycosis (PCM) is the most important systemic mycosis in Latin America. About 80% of PCM patients are present with its chronic form. The lungs are affected in most patients with the chronic form; however, pleural involvement has rarely been reported. We describe nine cases of PCM that presented with lung involvement and spontaneous pneumothorax. All patients, except one whose condition was not investigated, were smokers. PCM was diagnosed during the pneumothorax episode in three patients, and from 3 to 16 years before the pneumothorax episode in six patients. A total of six patients underwent chest drainage and one died as a direct result of the pneumothorax. We suggest that pneumothorax, although rare, should be considered in PCM patients who present with suddenly worsening dyspnoea. PCM should also be investigated in cases of pneumothorax in adult men from mycosis-endemic areas.
Keywords: lung mycosis; Paracoccidioides spp.; paracoccidioidomycosis; pneumothorax